Sing Your Heart Out: community singing as part of mental health recovery. Issue 3 (25th November 2017) - Shakespeare, Tom; Whieldon, Alice
Abstract : This paper reports on a qualitative evaluation of a Norfolk-based network of community singing workshops aimed at people with mental health conditions and the general public. The aims of the study were (a) to evaluate the effectiveness of the Sing Your Heart Out (SYHO) project and (b) to identify the key features which made the project distinctive. The study draws on 20 interviews with participants, two focus groups with organisers and workshop leaders, and participative observation over a 6-month period. Interviewees all reported improvement in or maintenance of their mental health and well-being as a direct result of engagement in the singing workshops. For most it was a key component, and for some the only and sufficient component in their recovery and ongoing psychological stability. SYHO was regarded as different from choirs and from most other social groups and also different from therapy groups, music or otherwise. The combination of singing with an inclusive social aspect was regarded as essential in effecting recovery. The lack of pressure to discuss their condition and the absence of explicit therapy was also mentioned by most participants as an important and welcome element in why SYHO worked for them. The combination of singing and social engagement produced an ongoing feeling of belonging and well-being. Attendance provided them with structure, support and contact that improved functioning and mood. We conclude that the SYHO model offers a low-commitment, low-cost tool for mental health recovery within the community.